The Safety and Efficacy of Absorb Bioresorbable Vascular Scaffold: A Systematic Review. Issue 1 (23rd September 2015) - Lu, Chang; Filion, Kristian B.; Eisenberg, Mark J.
ABSTRACT: Bioresorbable stents are novel devices designed to overcome the long‐term limitations of permanent stent implantation. The Absorb bioresorbable vascular scaffold (BVS; Abbott Vascular, Santa Clara, CA) was the first bioresorbable stent with Conformité Européenne mark approval in coronary vessels and has been the subject of multiple clinical studies. Despite its potential advantages, the safety and efficacy of BVS remain unclear. To address this, we conducted a systematic review to examine the safety and efficacy of BVS. The MEDLINE, Embase, Current Index to Nursing & Allied Health Literature (CINAHL), Cochrane, and Science Citation Index Expanded (SCIE) databases were searched for studies examining BVS safety and efficacy. Our search was restricted to studies published in English or French. Outcomes of interest include cardiac death, myocardial infarction, target‐lesion revascularization, restenosis, and composite endpoints. Eleven studies met our inclusion criteria (n = 2990), which included 1 randomized controlled trial and 10 cohort studies (2 controlled). These studies varied in size (11–1189) and follow‐up duration (1–60 months). The incidence of major adverse cardiac events ranged from 2.6% to 15.5%, with no statistically significant difference between BVS and control in studies that included a comparison group. Although available data are limited, current evidence is promising and suggests that the use of BVS is not associated with a significant increase in major cardiac events in the short term. Numerous randomized controlled trials are currently in progress that will further improve our understanding of the safety and efficacy of this device.